Gendered identity formation in post-colonial France: the case of French Muslims of Maghrebi origins with a focus on Algeria - Chaichian, Mohammad A. (Culture and religion, 2019)
In this article, we examine identity formation processes among French Muslims from former North African French colonies, focusing on Algeria. France's violent colonial presence in Algeria has put an indelible effect on three generations of French of Algerian origin, as they have struggled to survive despite political pressures and cultural demands in post-colonial France. Using several theories and concepts pertaining identity formation among colonial subjects, including Stuart Hall's discussion of "self-othering," Frantz Fanon's Manichaean notions of "black" and "white" identity formations, and W.E.B. Du Bois' concept of "double consciousness," we first analyse formation of a hybrid identity among three generations of French Muslims. Next, we focus on the torturous journey of French Muslim women particularly related to the hijab controversy, as they oscillate between resistance and assimilation under French Republic's Laïcité laws. We further examine the intersectionality of gender-based, religious and rural/tribal identities in Algeria, signified by two clearly delineated ‘gendered' public and private spaces, and boundary erosions between the two in post-colonial France. We conclude that under the false pretence of "gender equality," in its attempt to unveil Muslim women the French government is using their bodies as a cultural battleground to subject them to total submission and assimilation.